New Builders Leader and Electricians Journal, 1941 (1941)
1941 1939-1945 "New Builders Leader and Electricians Journal, 1941" [HFR0231], 1941 This rank and file magazine for building workers originated in the Minority Movement of the 1930s. This issue covers working conditions in a number of trades and problems relating to dilution and the employment of Irish and women workers.